Trucktown: Uh-Oh, Max - Scieszka, Jon; Shannon, David; 1959-; Long, Loren; Gordon, David; 1965 January 22-; Design Garage (Minneapolis, Minnesota, 2016)
"Max is having so much fun that he keeps getting stuck! Will anyone in Trucktown be able to help him out?"--Page [4] of cover.
Keywords: Trucks; Traffic accidents; Fiction; Fiction; Trucks; Juvenile fiction; Traffic accidents; Juvenile fiction; Trucks; Traffic accidents; Juvenile works; Fiction